The Use of LMS and Talking Stick Method to Improve Reading Skill for ESP Students - Kurnia; Sianna; Hamzar; Muh Ferils; Furqan (Hasanuddin University, 2023)
The Muhammadiyah University of Mamuju has been using LMS since the beginning of the pandemic, called SIMAK UNIMAJU. Learning processed can be accessed with an internet connection via mobile phones, notebooks, or by visiting internet cafes. In face-to-face learning after the pandemic, University lectures of ESP need to rethink student motivation strategies). This study combines the talking stick learning method and SIMAK UNIMAJU LMS technology in teaching reading. The objective of the research are the talking stick combine LMS Simak Unimaju improve the students ability, create students activity in acquiring intellectual skills and attitudes besides motor skills. Mix method design applied by using triangulation by one group pre-test and post-test design. The quantitative data were obtained by students' scores in English reading pre-test and post-test of recount text. Meanwhile, the qualitative data were obtained from classroom observation and interviews. The study was conducted at Class F Management Students in Universitas Muhammadiyah Mamuju, which involved 24 students. The findings showed that the hypothesis testing proved that t count ≥ ttable 14,29 ≥ 1.714. Therefore, the null hypothesis was rejected. It means using LMS and the talking stick method could improve students' ability in English reading comprehension. Another finding also showed that students' responses were positive. They responded that combining LMS and talking sticks is more enjoyable, motivating them to study. Furthermore, it helps them understand recount text and LMS combine talking stick method could be applied as one of the teaching readings to be implemented in the following semester.